2008
DOI: 10.1021/np700713r
|View full text |Cite
|
Sign up to set email alerts
|

Steroids and Flavonoids from Physalis alkekengi var. franchetii and Their Inhibitory Effects on Nitric Oxide Production

Abstract: Four new steroidal compounds possessing a rare 13,14-seco-16,24-cycloergostane skeleton, physalin Y ( 1), physalin Z ( 2), physalin I ( 6), and physalin II ( 7), were isolated from the 80% EtOH extract of calyces from Physalis alkekengi var. franchetii together with 11 known steroids ( 3- 5 and 8- 15) and eight flavonoids ( 16- 23). The structures of the new compounds were elucidated primarily on the basis of 1D and 2D NMR and mass spectroscopic studies. The relative configuration of the 3-OH group of 3, 4, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
75
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 107 publications
(79 citation statements)
references
References 24 publications
3
75
0
1
Order By: Relevance
“…The presence of this compound in the aerial part of P. alkekengi is being reported here for the first time, whereas physalin D has been previously isolated from the aerial parts of P. minima, P. angulata, and P. lancifolia (Row et al, Kawai et al, 1987Kawai et al, , 2001Makino et al, 1995a). The isolation of physalin D from the calyces of the plant is consistent with the results reported by Qiu et al (2008). According to our results, the methanol extract of P. alkekengi has strong antibacterial activity against Gram-positive bacteria.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…The presence of this compound in the aerial part of P. alkekengi is being reported here for the first time, whereas physalin D has been previously isolated from the aerial parts of P. minima, P. angulata, and P. lancifolia (Row et al, Kawai et al, 1987Kawai et al, , 2001Makino et al, 1995a). The isolation of physalin D from the calyces of the plant is consistent with the results reported by Qiu et al (2008). According to our results, the methanol extract of P. alkekengi has strong antibacterial activity against Gram-positive bacteria.…”
Section: Resultssupporting
confidence: 90%
“…Our report is the first for physalin D. Previous phytochemical studies on the aerial parts of Physalis plants have led to the identification of physalins, which are believed to be the bioactive compounds of the genus Physalis (Januário et al, 2002;Dos Santos et al, 2003;Wu et al, 2004;Choudhary et al, 2005;Lee & Houghton, 2005;Magalhaes et al, 2006;Damu et al, 2007;Castro et al, 2008). However, there is relatively little information in the literature regarding the steroid content of the calyces of Physalis species (Dinan et al, 1997;Qiu et al, 2008). In the present study, physalin D was isolated from the extracts of P. alkekengi.…”
Section: Resultsmentioning
confidence: 65%
“…The molecular formula of 2 was determined to be C 28 H 32 O 12 on the basis of HREIMS (m/z 560.1854, [M] + ; calcd 560.1894) and NMR data ( Table 1). The NMR data of 2 were similar to those of physalin Z 22 , and the differences between them were two of the double-bond carbon signals in physalin Z were replaced by two oxygenated methine signals in 2 located at C-6 and C-7, which were deduced by (Figure 2) of H-6/H-7 and H-7/H-8β revealed that OH-C(6) and OH-C(7) were α-oriented. So the structure of compound 2 was deduced and named as physalin IV (2).…”
Section: Resultssupporting
confidence: 56%
“…Hence, the structure of compound 3 was identified to be 3-O-methylphysalin X (3). The structures of five known steroidal compounds, physalin Z (4) 22 , physalin C (5) 24 , physalin I (6) 25 , physalin P (7) 26 , 25,27-dihydro-4,7-dedehydro-7-deoxyneophysalin A (8) 27 , were elucidated in comparison to their spectroscopic data with those reported in the literature.…”
Section: Resultsmentioning
confidence: 99%
“…franchetii. Physalins W (306) and X (307) were initially isolated by Chen et al (147) and their structures revised by Qiu and coworkers (139). The latter authors also reported the isolation of the 3-methoxy analogues physalin I (308) and physalin II (309).…”
Section: Neophysalins and Cyclophysalinsmentioning
confidence: 99%